A comprehensive thermo-viscoelastic experimental investigation of Ecoflex polymer. (June 2020) - Liao, Zisheng; Hossain, Mokarram; Yao, Xiaohu; Navaratne, Rukshan; Chagnon, Gregory
Abstract: Silicone polymers have enormous applications, especially in the areas of biomedical engineering. Ecoflex, a commercially available room temperature cured silicone polymer, has attracted considerable attention due to its wide range of applications as medical-grade silicones and as matrix materials in producing nano-filled stretchable sensors and dielectric elastomers for soft robotics. In this contribution, we have conducted a wide range of experiments under thermo-mechanical loadings. These experiments consist of loading–unloading cyclic tests, single-step relaxation tests, Mullins effects tests at different strain rates and stretches, stress recovery tests at different rest time, etc. In order to assess the temperature influences on Ecoflex, a number of viscoelastic tests are performed in a thermal chamber with temperature ranging from -40 ° C to 140 ° C. Extensive experimental findings illustrate that Ecoflex experiences a significant stress softening in the first cycles and such a softening recovers gradually with respect to time. It also shows a significant amount of cyclic dissipations at various stretch levels as well as a considerable stress relaxation only for virgin samples. Cyclic dissipations and stress relaxation almost disappear for the case of pre-stretched samples. Furthermore, the material is more or less sensitive under a wide range of temperature differences. Highlights: A thorough experimental characterization of Ecoflex polymer. Strain rate and temperature influences are analysed. Stress softening and recovery behaviour have been identified. Ecoflex shows minimum viscoelastic dissipative behaviour. Stress relaxation of Ecoflex lasts for more than twelve hours.